High-performance liquid chromatographic method with amperometric detection employing boron-doped diamond electrode for the determination of sildenafil, vardenafil and their main metabolites in plasma - Bartošová, Zdenka; Jirovský, David; Horna, Aleš (Journal of chromatography. A, Including electrophoresis and other separation methods, 2011)
A simple, fast and sensitive HPLC method with electrochemical detection employing boron-doped diamond electrode (BDD) for the determination of sildenafil (Viagra™), vardenafil (Levitra™) and their main metabolites, N-desmethyl sildenafil and N-desethyl vardenafil in human plasma is presented. The assay involved drug extraction by tert-butyl methyl ether and isocratic reversed-phase liquid chromatography with amperometric detection. Complete separation of all analytes was achieved within 12 min. The mobile phase consisted of 20mM sodium dihydrogen phosphate with 40 mM sodium perchlorate/acetonitrile (70:30, v/v), pH 3.5. The electrode working potential was +1520 mV (vs. Pd/H(2)). Calibration curves were linear over the concentration range of 10-400 ng mL(-1). Phloretin was used as an internal standard. The limits of detection (LOD) and quantification (LOQ) for the studied analytes were within the range of 2-4 ng mL(-1) and 7.0-13.4 ng mL(-1), respectively. The developed method was applied to human plasma samples spiked with analytes at therapeutic concentrations. The study confirms the method's suitability for both pharmacokinetic studies and therapeutic monitoring.
Keywords: diamant; Hydrogen-Ion Concentration; Chromatography, Reverse-Phase; Linear Models; piperaziny; Boron; vysokoúčinná kapalinová chromatografie; puriny; sulfony; lidé; Sensitivity and Specificity; Sulfones; chromatografie s reverzní fází; Diamond; senzitivita a specificita; lineární modely; Triazines; Imidazoles; Chromatography, High Pressure Liquid; Electrodes; Piperazines; Purines; triaziny; elektrody; bor; koncentrace vodíkových iontů; imidazoly; Humans